Social welfare and poverty alleviation some reflections. - Naik, Chitra (1996)
"As most of the welfare needs arise from poverty, poverty alleviation has to be country's main agenda for welfare and upgradation of standard of living. Involvement of voluntary agencies, mass media and the corporate sector with "mission mode" approach is vital for the success of poverty alleviation programmes"
Keywords: Social problems - India; Social service - India; Poverty - India; Poverty